2018
DOI: 10.1021/acs.jafc.7b06082
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Metabolomics of Type 2 Diabetic Rats and Treatment with Gardenia jasminoides Ellis Based on Mass Spectrometry Technique

Abstract: Modern studies have indicated Gardenia jasminoides Ellis (G. jasminoides) showed positive effect in treating type 2 diabetes mellitus (T2DM). In this study, 60 streptozotocin-induced T2DM rats were divided into four groups: type 2 diabetes control group, geniposide-treated group, total iridoid glycosides-treated group, and crude extraction of gardenlae fructus-treated group. The other ten healthy rats were the healthy control group. During 12 weeks of treatment, rat's feces samples were collected for the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…It has previously been reported that the enhanced metabolism of branched amino acids and aromatic amino acids increased the risk of T2DM and obesities [26,27], which are positively correlated with insulin resistance (IR) and hyperglycemia [3,[28][29][30]. In our study, valine, leucine, and isoleucine metabolism; phenylalanine, tyrosine, and tryptophan biosynthesis; and phenylalanine metabolism showed overexpression in the model group according to metabolomics and PICRUSt analysis.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 52%
See 1 more Smart Citation
“…It has previously been reported that the enhanced metabolism of branched amino acids and aromatic amino acids increased the risk of T2DM and obesities [26,27], which are positively correlated with insulin resistance (IR) and hyperglycemia [3,[28][29][30]. In our study, valine, leucine, and isoleucine metabolism; phenylalanine, tyrosine, and tryptophan biosynthesis; and phenylalanine metabolism showed overexpression in the model group according to metabolomics and PICRUSt analysis.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 52%
“…In several studies, it was revealed that increased sphingosine-1-phosphate (S1P) occurs to obese animals and humans, which can lead to IR and overexpression of sphingolipid (SL) metabolism [46]. The sphingolipid metabolism is altered in T2DM and relating to cell death [26]. However, our results obtained from metabolomics analysis were different from those published in some previous studies, which may be due to the following: first, it has been reported that the environment can influence SL levels [47], and most of the previously performed studies were carried out based on biological fluid and tissues, which is different from that used in our study.…”
mentioning
confidence: 99%
“…We defined an integrated biomarker (2‐acetolactate, 2‐hydroxy‐2,4‐pentadienoate, L‐arabinose and L‐glutamine) for diagnosing IFG and T2DM by evaluating 17 potential biomarkers with the biomarker model. Differential pathway analysis revealed that the progression of diabetes was mainly related to amino acid metabolism: the levels of L‐alanine, L‐arginine, L‐proline, L‐phenylalanine and 2‐hydroxy‐2,4‐pentadienoate were increased, which was consistent with other reports 29–31 …”
Section: Discussionsupporting
confidence: 90%
“…Nowadays, metabolomics are widely used to discriminate the profiles of chemical constituents and reveal the mechanism of action involved in herb processing. For example, metabolomics studies using reverse-phase liquid chromatography quadrupole-time of flight (RPLC-Q-TOF)/Mass Spectrometry (MS) to investigate chemical markers after processing of Radix aconite (Li et al, 2013), and the potential treatment mechanism of GF against type 2 diabetes in rats via targeted metabolome profiling and fecal metabolomics (Wang et al, 2017; Zhou et al, 2018). In this study, we initially used a rat model of ethanol-induced acute stomach ulcer treated with GF and GFC.…”
Section: Introductionmentioning
confidence: 99%